System dynamics simulations for data-intensive applications. (October 2017) - Neuwirth, Christian
Abstract: Simulation modeling is increasingly perceived as a methodological asset to the field of data science. Nonetheless, adequate graphical database interfaces are missing especially for most System Dynamics (SD) simulation tools. SimSyn is freely available middleware used to link together models developed in VENSIM with a PostgreSQL database for spanning SD models over geographic or multi-dimensional parameter space. The capabilities of SimSyn are demonstrated by simulating terrestrial carbon storage for 10, 000 years on a 5 arc-min raster mesh with 278, 115 grid cells. Results indicated the reasonable performance of data-linked simulations (7, 500 to 10, 000 runs per 15 min) and a considerable increase of computational overheads associated with additional time series inputs. Apart from increasing performance, the incorporation of SD interoperability standards is a key objective for the further development of SimSyn.